2000
DOI: 10.1007/s11663-000-0018-y
|View full text |Cite
|
Sign up to set email alerts
|

Examination of solidification pathways and the liquidus surface in the Nb-Ti-Al system

Abstract: The solidification pathways, subsequent solid-state transformations, and the liquidus surface in the Nb-Ti-Al system have been examined as part of a larger investigation of phase equilibria in Nb-TiAl intermetallic alloys. Fifteen alloys ranging in composition from 15 to 40 at. pct Al, with Nb to Ti ratios of 4:1, 2:1, 1.5:1, 1:1, and 1:1.5, were prepared by arc melting and the as-cast microstructures were characterized by optical microscopy (OM), microhardness, X-ray diffraction (XRD), differential thermal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Compared to the thermodynamic descriptions by Kattner [4] and Servant and Ansara [6] the primary ␤ field extends further towards the Al-rich corner, while correspondingly the fields of primary ␣, and ␦ are less extended. The limit of the primary -phase field proposed by [54] to be at 20 at.% Ti is not fully confirmed by Fig. 14. The ␤-transus surface of the Al-Nb-Ti system projected on the Gibbs triangle, with isotherms given in K: within the shadowed area the ␤-phase is ordered, i.e.…”
Section: Liquidus Solidus Andˇ-transus Surfacesmentioning
confidence: 82%
See 1 more Smart Citation
“…Compared to the thermodynamic descriptions by Kattner [4] and Servant and Ansara [6] the primary ␤ field extends further towards the Al-rich corner, while correspondingly the fields of primary ␣, and ␦ are less extended. The limit of the primary -phase field proposed by [54] to be at 20 at.% Ti is not fully confirmed by Fig. 14. The ␤-transus surface of the Al-Nb-Ti system projected on the Gibbs triangle, with isotherms given in K: within the shadowed area the ␤-phase is ordered, i.e.…”
Section: Liquidus Solidus Andˇ-transus Surfacesmentioning
confidence: 82%
“…The liquidus surface of the Al-Nb-Ti system showing (a) primary phase fields (points are experimental data of[25,27,38,[51][52][53][54] and present work (PW) and (b) projection of isotherms (in K) and univariant lines on the Gibbs triangle.…”
mentioning
confidence: 99%
“…The updated version of the Al-Ti phase diagram [2005Rag] depicts a number of intermediate phases. TiAl 3 has two crystal modifications.…”
Section: Binary Systemsmentioning
confidence: 99%
“…A complete liquidus projection of this ternary system was reported by [1989Kal], followed by more experimental results by [1990Per], a computed projection by [1992Kat], a partial projection by [1992Pav1], and a reinvestigation by [1995Zdz] and[2000Leo1]. [1990Per] arc-melted alloys under an Ar atmosphere.…”
Section: Liquidus Projectionmentioning
confidence: 99%
“…The majority of the available experimental data for the high-temperature equilibrium was reported by Perepezko et al [14], Zdziobek et al [15] and Leonard et al [16,17]. Recently, we have experimentally demonstrated that the b phase field on the liquidus projection should be expanded by pushing the univariant L + b + c liquidus reaction to higher Al compositions [18].…”
Section: Introductionmentioning
confidence: 88%